ANALISIS PENGHITUNGAN INFLASI BERDASARKAN BERDASARKAN PRODUK DOMESTIK REGIONAL BRUTO (PDRB) SUMATERA SELATAN PERIODE 2001 - 2011 - Nazeli Adnan (Department of Development Economics, Universitas Sriwijaya, 2013)
This research aims to analyze the inflation calculation is based on Gross Domestic Product (GDP) of South Sumatra 2001-2011. The data used in this study is secondary data, that is data of GDP at current prices, constant prices GDP and Inflation in South Sumatra. In this study used two data analysis tools, namely the qualitative analysis and quantitative analysis. Qualitative analysis explains the good development of the South Sumatra GDP based on current prices and constant prices and inflation that occurred during the period 2001 - 2011 in the form of tables and linked to relevant theory. Quantitative analyzes using mathematical approaches, such as using the formula GDP growth and inflation projections and formulas of these variables. Results showed during the period of 2007 to 2011 GDP at current prices and constant prices has increased (positive growth), despite constant price GDP growth is not as sharp as partumbuhan GDP at current prices. Average growth of GDP at current prices was 13.62% while the constant price GDP consume is 5.33% per year ah. Keywords: Inflation, Gross Regional Domestic Product (GRDP)